Implementing the Contextual Learning Activity ‘Shopping with Mom’ to Improve Fifth Grade Students’ Activeness in Learning Number Material at SDN Junrejo 01 Batu - Faizah, Putri Nur; Faizah, Maryam (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v10i1.3645, 2025)
This study aims to observe the improvement in students’ active engagement through the implementation of the contextual learning activity innovation “Shopping with Mom” on whole number material for fifth-grade students at SDN Junrejo 01 Batu. This research is expected to provide new insights into more creative learning methods and assist educators in addressing the challenges of low student engagement in mathematics learning. The study employs a classroom action research (CAR) method, conducted in Class V A of SDN Junrejo 01 Batu during the 2024/2025 academic year, involving 20 students and focusing on mathematics material related to whole numbers up to 1,000,000. The final result of the action in Cycle 2 showed improvement, with an average evaluation score of 85.5, compared to 74.5 in Cycle 1. The percentage of learning mastery increased from 60% in Cycle 1 to 85% in Cycle 2. Based on these results, it can be concluded that the contextual learning activity innovation “Shopping with Mom” effectively increased students’ active engagement in learning whole numbers up to 1,000,000. Therefore, the research is considered successful and was stopped at Cycle 2